The Effectiveness of Earth and Building Tax Collection in Takalar District - Irfan Irfan; Jumalia Mannayong; Haerul Haerul (Universitas Negeri Makassar, 2019)
Regional autonomy gives the region the right to determine its own direction and development goals in the area. This research aims to analyze and discuss the Effectiveness of Land and Building Tax Collection in Takalar Regency. The research method used is qualitative with a Case Study approach. Data Collection and Validation Techniques are carried out by; observation, interview, and documentation. The data analysis technique used in this study is the analysis that is carried out continuously both in the process of collecting data and after the data collection has been completed. The data analysis process used in this study is data condensation, data display, and conclusion drawing/verifications. The results of the study are based on the Source Approach of the Takalar District Financial Management Agency in terms of human resources and the source of facilities and infrastructure which are considered to be still relatively low/insufficient in the management of increased PBB collection.